A Review on Hydrogen Generation by Photo-, Electro-, and Photoelectro-Catalysts Based on Chitosan, Chitin, Cellulose, and Carbon Materials Obtained from These Biopolymers - Keshipour, Sajjad; Hadidi, Mina; Gholipour, Ozra (Advances in polymer technology, 2023)
Biopolymer-based catalysts like chitosan, chitin, and cellulose offer sustainability and high efficiency both as the catalyst or catalyst support in a broad range of applications, especially in hydrogen evolution reactions. This review focused on hydrogen evolution catalysts of chitosan, chitin, cellulose, and carbon materials obtained from these biopolymers to highlight the opportunities of these sustainable catalysts in this field. All the reports in this area could be classified as one of the photocatalysts, electrocatalysts, and photoelectrocatalysts, and their mechanisms were clarified in the beginning. Then, the results of catalysts obtained from each of these biopolymers were discussed separately to reveal the roles of the biopolymers. It was concluded that all of the biopolymers enjoy some common benefits like hydrogen bonding, chelating with transition metals, easy chemical modification, high performance, and potential to be used as the precursors of carbon or porous materials. Among them, chitosan showed outstanding merit due to the better performance in metal grafting, amendment, and ability of hydrogen bonding. Moreover, it provides highly active nitrogen-doped carbon as the support of transition metals in the hydrogen generation, enhancing the reaction rate by retarding the charges recombination.